MODELING TOWARDS PENTAVALENT VACCINE COVERAGE IN PAKISTAN - Muhammad Imran; Jamal Abdul Nasir; Abid Ali Chohan (Journal of University Medical & Dental College, 2016)
ABSTRACTOBJECTIVES: To expose the trend and proposing the forecasting model for monthly pentavalent infant immunization coverage a signiﬁcant concern in disease management and control. DESIGN: The reported data of monthly infant pentavalent immunization coverage to National institute of health, Islamabad, Pakistan from January 2009 to October 2014 for the present study has been taken from Pakistan bureau of statistics with total time series entities 70. National institute of health, Islamabad took the record of per month number of doses administered (0-11 months) children by the registered health centre in Pakistan. PERIOD: January 2009 to October 2014. SETTING: Pakistan Bureau of Statistics (Statistics House) METHODS: Two time series techniques namely Box Jenkins and artiﬁcial neural network (ANN) has been carried out to develop a forecasting model. Results: ARIMA (1, 1, 1) model with RMSE (56998) and ANN 10-3-1 model with RMSE (34582) are selected after execution of various set of parameters of both techniques.Due to lower RMSE ANN 10-3-1 is an adequate model. The established ANN model revealed that the increment for infant pentavalent coverage is 4.14% expected in next six month. CONCLUSIONS: ANN 10-3-1 is an efﬁcient model for forecasting the monthly pentavalent infant immunization coverage in Pakistan.